Memórias da Banda: percursos de formação de ex-integrantes - Silva, Rodrigo Lisboa da (2020)
Marching bands are musical and educational manifestations present in the daily life of several schools - generally, as extracurricular activities. They provide opportunities to make music through instrumental practice, being capable of referring several of their students and former students to a future professionalization in music. However, not everyone wants to pursue music as a profession or enter an undergraduate course in the field. Therefore, this is a qualitative research with ten former members of marching bands in the city of João Pessoa-PB – five individuals who continued to maintain contact with their band, eventually participating in musical performances; five individuals who no longer participated in band activities. The objective of this research to investigate the perceptions and experiences of former members of marching bands – who did not follow higher or professional studies or a career in the field – regarding their musical education paths. The specific objectives were defined as follows: discuss the marching band as an activity that facilitates access to music education; identify the expectations and motivations that led the students to join a marching band; analyze the subjective meanings of their relationship with music at different times in their lives, especially in the marching band; analyze the possible limits of the experiences in bands highlighted by the former members. As a data collection instrument, narrative interviews were used to learn about the respective musical training of these former members. Besides, a second semi-structured interview was performed, as a source of complementary data that allowed to focus and go further into some information revealed in the narrative interviews. The final analysis was constructed through the intersection of the subjects' reports in dialogue with the studies in the area of education, music education, and psychology (Logotherapy), presented and discussed in the chapters dedicated to the bibliographic source. In this regard, the analysis and discussion of the data address issues such as motivations for joining the band; adoption of selection tests based on previous musical skills; teaching and learning processes; abandonment and current feelings, and relationships with music and/or bands. It is discussed how participation in bands can bring several contributions that are part of the memory of its former members until today - favoring social interactions; development of affective bonds and values; opportunity to participate in presentations and trips; access to musical learning. However, the research subjects also point out some limits present in the practices of these groups - the adoption of a repetitive repertoire; authoritarianism of the conductor; indiscipline and rivalry; pedagogical lack of preparation; lack of incentive, and investment. This study can contribute to the understanding of bands as significant spaces in the lives of their participants and also as important contexts for access to music teaching and the development of non-musical skills and abilities. Moreover, the research also shows that many of the current practices in the bands need to be rethought to favor a more democratic, comprehensive, and, thus, better pedagogically oriented music education.